Hubungan Kondisi Lingkungan Belajar Dengan Minat Belajar Peserta Didik di LKP Prima Data Kota Padang - Amanda Shalsabila Adzami Zahri; Setiawati Setiawati (Jurnal Family Education, 2023)
This research is motivated by the low interest in student learning, this is thought to be caused by a less conducive learning environment. This study aims to (1) describe the conditions of the learning environment (2) describe students' learning interests (3) describe the relationship between the learning environment and students' learning interests at LKP Prima Data Padang City. approach with a correlational type. The population of this study were all students registered at LKP Prima Data Padang City for the 2022/2023 academic year, totaling 38 people. The sampling technique used cluster random sampling and 50% of the population, totaling 19 people, was taken. Data collection techniques using questionnaires and data collection tools in the form of a list of statements. Data analysis techniques use percentages and rank order. The results of this study indicate that (1) the condition of the learning environment at LKP Prima Data is categorized as unfavorable. (2) students' interest in LKP Prima Data is low. (3) The results of data processing show that there is a significant relationship between the conditions of the learning environment and the interest in learning at LKP Prima Data Padang City